Systematic review of hydroxychloroquine use in pregnant patients with autoimmune diseases - Shapiro Deborah; Chao Chun; Hom Christine; Sperber Kirk; Ash Julia (BMC, 2009)
Abstract Objective The purpose of this study is to compare the incidence of congenital defects, spontaneous abortions, number of live births, fetal death and pre-maturity in women with autoimmune diseases taking HCQ during pregnancy. Methods The authors searched MEDLINE, Cochrane data base, Ovid-Currents Clinical Medicine, Ovid-Embase:Drugs and Pharmacology, EBSCO, Web of Science, and SCOPUS using the search terms HCQ and/or pregnancy. We attempted to identify all clinical trials from 1980 to 2007 regardless of language or publication status. We also searched Cochrane Central Library and http://www.Clinical trials.gov for clinical trials of HCQ and pregnancy. Data were extracted onto standardized forms and were confirmed. Results The odds ratio (OR) of congenital defects in live births of women taking HCQ during pregnancy was 0.66, 95% confidence intervals (CI) 0.25, 1.75. The OR of a live birth for women taking HCQ during pregnancy was 1.05 (95% CI 0.58, 1.93). The OR of spontaneous abortion in women taking HCQ during pregnancy was 0.92 (95% CI 0.49, 1.72). The OR of fetal deaths in women taking HCQ during pregnancy was 0.97 (95% CI 0.14, 6.54). The OR of pre-mature birth defined as birth before 37 weeks in women taking HCQ during pregnancy was 1.10 (95% CI 0.75, 1.61). Conclusion HCQ is not associated with any increased risk of congenital defects, spontaneous abortions, fetal death, pre-maturity and decreased numbers of live births in patients with auto-immune diseases.